Influence of Electronic Monitoring and Evaluation on Administrative Decision-Making in the Educational Sector - Kasimu, Salihu; Maijama'a, Ladan; Hamisu, Idi; Abubakar, Abdulkadir (Darul Yasin Al Sys, 2025)
This study investigates the essential role of Electronic Monitoring and Evaluation (EMAE) in enhancing the elementary education sector. EMAE frameworks offer systematic methodologies for assessing educational programs, fostering accountability, and facilitating data-driven decision-making. This research serves as a case study of the primary education authority in Bauchi Local Government, with a particular focus on their teachers. According to the 2023 Annual School Census, there are 4,226 staff members, from which 367 were sampled using the Yamane formula. The sampling frame was stratified to reach the target respondents effectively. Data were collected using a structured questionnaire comprised of closed-ended questions that were designed and validated, achieving a Cronbach’s Alpha of 0.83. Based on 358 completed questionnaires, the responses were analyzed using descriptive and inferential statistics. The findings emphasize how effective EMAE practices can lead to improved educational outcomes by identifying successful teaching strategies and fostering continuous enhancement. Additionally, the involvement of diverse stakeholders—including educators, parents, and community members—strengthens collaboration and ensures that educational reforms remain relevant and sustainable. The results highlight the significance of EMAE in aligning national education systems with global standards, such as the Sustainable Development Goals (SDGs). Ultimately, this research underscores that robust EMAE practices are essential for cultivating an effective, responsive, and equitable educational environment, ensuring that all students receive a quality education.